Scaling community-based aquaculture for enhanced nutrition and women’s empowerment: lessons from Odisha, India - Dubey, Sourabh Kumar; Padiyar, Arun; Chadag, Vishnumurthy Mohan; Shenoy, Neetha; Gaikwad, Amar Bharat; Ratha, Baishnaba Charan; Belton, Ben (Frontiers in Sustainable Food Systems, 2024)
Introduction: Aquatic foods, particularly fish, are essential for addressing malnutrition, especially in vulnerable populations like children and women. In India, traditional aquaculture practices centered around carp species often overlooked the production of nutrient-rich small fish. To address this, nutrition-sensitive aquaculture approaches advocate for integrating species like mola carplet (Amblypharyngodon mola) rich in micronutrients, into existing systems. In Odisha, India, where poverty and food insecurity are prevalent, the government initiated a program to empower women through aquaculture, focusing on nutrition-sensitive carp-mola polyculture in community ponds through Women Self-Help Groups (WSHGs).Methods: This study evaluates the effectiveness of this government program in enhancing income, household nutrition, and women's empowerment. Data from field surveys conducted across all 30 districts of Odisha were analyzed to assess participation, capacity building, adoption of better management practices (BMPs), productivity of carp-mola polyculture, household fish consumption, and profitability.The study found widespread participation and adoption of BMPs among WSHGs, leading to increased productivity and income. Carp-mola polyculture systems showed higher productivity and consumption rates, contributing to improved nutrition among WSHGs and their communities. Despite challenges such as input costs and limited mola availability, WSHGs reported profitability from fish farming, with carp-mola polyculture systems yielding higher net income. Factors influencing productivity and profitability included water retention period, stocking density, feed application, and training. The program's impact extended beyond economic benefits, encompassing environmental improvement, women's empowerment, and enhanced nutrition outcomes. The study highlights the success of the government program in promoting sustainable aquaculture practices and improving nutrition outcomes in Odisha. Continued support, capacity building, and collaboration among stakeholders are essential for scaling up nutrition-sensitive aquaculture interventions and ensuring long-term sustainability. Strengthening dissemination processes, addressing challenges, and further research on small indigenous fish production techniques are crucial for maximizing the program's impact on food security and rural development.